Piracy and law in the Ottoman Mediterranean - White, Joshua M. (Stanford University Press, 2018)
The 1570s marked the beginning of an age of pervasive piracy in the Mediterranean that persisted into the eighteenth century. By 1700, the limits of the Ottoman Mediterranean were defined not by Ottoman territorial sovereignty or naval supremacy, but by the reach of imperial law, which had been indelibly shaped by the challenge of piracy. Joshua M. White plumbs the depths of these uncharted, frequently uncatalogued waters, revealing how piracy shaped both the Ottoman legal space and the contours of the Mediterranean world.